Edukasi 5S di Lingkungan SMK Plus Trimitsa Bersama Dosen dan Mahasiswa JGU - Ayu Nurul Haryudiniarti; Sinta Restuasih; Brainvendra Widi Dionova; Mohamad Zaenudin; Yasya Khalif Perdana Saleh (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
5S is a work culture from Japan that is easy to apply in daily activities, the 5S concept is simple so that it is easy for anyone to understand and understand. The introduction of 5S to Trimitsa Plus Vocational High School students was preceded by introducing what S consists of five parts, namely Seiri, Seiton, Seiso, Seiketsu and Shitsuke. The implementation of community service activities for SMK Plus Trimitsa students is a form of the JGU campus' contribution to the surrounding environment. This activity involved JGU campus students and lecturers who served as material presenters, escorted educational games about 5S and also helped implement 5S in the SMK Plus Trimitsa workshop. Students of SMK Plus Trimitsa are given the opportunity to ask questions and answers about 5S so that they can have the same understanding as the presenter of the material and games related to 5S, namely the game of arranging numbers and letters from boxes containing scattered numbers and letters. The aim is for students to be able to understand that there is a difference between messy and tidy working conditions where if a messy work environment will make it difficult for us to work.